2016
DOI: 10.1186/s12864-016-2735-x
|View full text |Cite
|
Sign up to set email alerts
|

Flashy flagella: flagellin modification is relatively common and highly versatile among the Enterobacteriaceae

Abstract: BackgroundPost-translational glycosylation of the flagellin protein is relatively common among Gram-negative bacteria, and has been linked to several phenotypes, including flagellar biosynthesis and motility, biofilm formation, host immune evasion and manipulation and virulence. However to date, despite extensive physiological and genetic characterization, it has never been reported for the peritrichously flagellate Enterobacteriaceae.ResultsUsing comparative genomic approaches we analyzed 2,000 representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 48 publications
(68 reference statements)
4
57
0
Order By: Relevance
“…Both the structure and function of the flagella were disrupted in separate, site‐specific mutations, as the actual flagellar filament may play a role in adhesion, whereas swimming motility allows the bacterial cell to overcome the natural repulsive forces that exist between itself and a surface, and also allows the cell to respond to chemotactic signals in the environment (O'Toole and Kolter, ; Ramos et al ., ). The flagellar filament has also been shown to be subject to flagellar glycosylation, which may play a role in the avoidance of host recognition during infection, host specificity, attachment and virulence (De Maayer and Cowan, ; Logan, ). Flagellar glycosylation occurs when N‐ and O‐linked carbohydrates are added to flagellin, the repeating major subunit of the filament, to change both its antigenic properties and function (Takeuchi et al ., ).…”
Section: New Insights Into the Pathogenicity Of P Ananatismentioning
confidence: 99%
“…Both the structure and function of the flagella were disrupted in separate, site‐specific mutations, as the actual flagellar filament may play a role in adhesion, whereas swimming motility allows the bacterial cell to overcome the natural repulsive forces that exist between itself and a surface, and also allows the cell to respond to chemotactic signals in the environment (O'Toole and Kolter, ; Ramos et al ., ). The flagellar filament has also been shown to be subject to flagellar glycosylation, which may play a role in the avoidance of host recognition during infection, host specificity, attachment and virulence (De Maayer and Cowan, ; Logan, ). Flagellar glycosylation occurs when N‐ and O‐linked carbohydrates are added to flagellin, the repeating major subunit of the filament, to change both its antigenic properties and function (Takeuchi et al ., ).…”
Section: New Insights Into the Pathogenicity Of P Ananatismentioning
confidence: 99%
“…Flagellin Methylation Islands (FMI) and thus modifications of flagellins by methylation are common in Enterobacteriaceae 18 . In addition to Salmonella , many bacterial species including Yersinia, Enterobacter, Franconibacter , and Pantoea contain chromosomal FMI loci, which encode orthologues of FliB.…”
Section: Discussionmentioning
confidence: 99%
“…by posttranslational modifications of flagellin. Flagellin glycosylation is relatively common among Enterobacteriaceae 18 , in Campylobacter, Aeromonas and Pseudomonas species 1921 and plays a critical role in adhesion, biofilm formation or mimicry of host cell surface glycans 22,23 . S. enterica does not posttranslationally glycosylate its flagellins.…”
Section: Introductionmentioning
confidence: 99%
“…Flagellin glycosylation is essential for flagellar filament formation and swimming motility in a range of Gram-negative bacterial taxa, as well as the Gram-positive relative Paenibacillus alvei [7, 8, 13]. The original descriptive publications of the genus Geobacillus indicated that the type strains of all the described species are all motile.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, glycosylation gene deletion in the opportunistic human pathogen Pseudomonas aeruginosa and plant pathogen Pseudomonas syringae had no direct effect on assembly or motility [11, 12]. As flagellin is a highly immunogenic protein recognised by the host during infection, flagellin glycosylation in Gram-negative pathogens can facilitate immune evasion [13, 14]. Other purported functions of flagellin glycosylation include surface recognition, attachment and adhesion, biofilm formation, increased resistance against proteolytic degradation and virulence [1517].…”
Section: Introductionmentioning
confidence: 99%